2015
DOI: 10.1186/s12348-015-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined systemic and ocular chemotherapy for anterior segment metastasis of systemic mantle cell lymphoma

Abstract: BackgroundMantle cell lymphoma (MCL) is an aggressive subtype of non-Hodgkin’s lymphoma that rarely metastasizes to the iris and the anterior segment. Blastic/pleomorphic morphology is thought to have an adverse effect on prognosis in MCL. MCL is resistant to conventional chemotherapeutic regimens with a tendency for multiple relapses. Management of anterior segment metastasis of systemic MCL has not been described in literature.FindingsA 58-year-old male presented with an aggressive, relapsing, metastatic, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…We showed that 1 mg of intravitreal rituximab in 0.1 cc (the 10 mg/cc concentration) not only was safe but also could treat vitreoretinal lymphoma. This was then confirmed by others [ 43 45 ]. There are no set protocols that have been verified in larger cohorts of patients.…”
Section: Treatmentsupporting
confidence: 78%
“…We showed that 1 mg of intravitreal rituximab in 0.1 cc (the 10 mg/cc concentration) not only was safe but also could treat vitreoretinal lymphoma. This was then confirmed by others [ 43 45 ]. There are no set protocols that have been verified in larger cohorts of patients.…”
Section: Treatmentsupporting
confidence: 78%
“…Ocular adnexal involvement of all NHL is clinically detectable in about 1.3–5% of cases, of which 5% have been found to be secondary to MCL. Intraocular involvement of MCL, notably, is extremely rare and has only been reported in 7 cases in the literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…Reid et al reported unilateral granulomatous anterior chamber inflammation and localized undulations of the iris with aberrant vasculature in an elderly male of systemic MCL [9]. Agarwal et al reported another MCL case presented with unilateral anterior chamber hypopyon, thickening of the iris and iris neovascularization [5]. Although malignancy was believed to mainly involve the iris in these cases [5, 79], ciliary body was the major site of MCL recurrence in our case as revealed by UBM, despite that a concomitant anterior chamber reaction was also observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations